Penilaian Sifat Fisik Daging Kerbau dengan Variasi Lama Perendaman dalam Ekstrak Bonggol Nanas: Evaluation of Physical Properties of Buffalo Meat by Varying The Length of Marination in Pineapple Pith Extract - Barus, Erdina Chyntia Br; Mega, Olfa; Sulaksana, Indra (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2025)
Background: Buffalo meat contains 18.7% protein, has a darker color than beef, buffalo fat is whiter with lower meat fat content, meat texture is tough, has larger, coarser, and denser fibers. Pineapple pith contains bromelain enzyme, a source of vitamin C which functions as an antioxidant and high fiber content. Marinating buffalo meat in pineapple pith extract is done to improve the physical quality of the meat. Purpose: The purpose of this research was to study the effect of marinating buffalo meat in pineapple pith extract on pH value, water holding capacity, and cooking loss. Methods: This study used a completely randomized design (CRD) consisting of 5 treatments and 4 replicates. The treatments were buffalo meat without marinating in pineapple pith extract (P0), buffalo meat with marinating in pineapple pith extract for 15 min (P1), 30 min (P2), 45 min (P3), and 60 min (P4). The concentration of pineapple stem extract was 20% (v/v). The data were analyzed by analysis of variance (ANOVA). Results: The results showed that the treatment did not significantly (P>0.05) affect the pH value, water holding capacity and cooking loss. The range of pH values obtained was 5.82-6.19, water holding capacity was 20.14%-24.86%, and cooking loss was 35.82%-39.77%, with the average pH values, water holding capacity, and cooking shrinkage were 5.94, 21.95%, and 38.66%, respectively. Conclusion: Marinating buffalo meat in pineapple pith extract at 20% concentration for up to 60 minutes did not change the pH value, water holding capacity and cooking loss.